The Effect of Recruitment and Teamwork on the Productivity of PT Kharisma Guna Makmur - Ririn Uke Saraswati (International Journal of Economics and Management Research, 2024)
This study aims to analyze the influence of Recruitment and Teamwork on Employee Productivity at PT Kharisma Guna Makmur. The research method used is quantitative by distributing questionnaires to 80 respondents. The data were analyzed using multiple linear regression. The results show that both Recruitment and Teamwork have a positive and significant influence on Employee Productivity, both partially and simultaneously. The coefficient of determination (R²) value of 0.875 indicates that 87.5% of the variation in productivity can be explained by the two variables. These findings highlight the importance of implementing effective recruitment and strengthening teamwork to optimally improve employee performanceKeywords: .